Analisis Kemiringan Tumpukan Material Belerang pada Area Open Storage PT. PKG Menggunakan Metode Natural Angle Of Repose - Rizqi Dimas Al’faiz; Akhmad Andi Saputra; Bana Evardius (Jurnal Kridatama Sains dan Teknologi, 2026)
The storage of sulphur material in open storage areas requires control of the pile’s slope to ensure stability and operational safety. This study aims to analyse the Natural Angle of Repose (AOR), evaluate the suitability of the actual slope, identify factors affecting the slope angle, and assess the stability of sulphur material piles at PT. PKG. The study employed a descriptive quantitative method by measuring the height and base radius of the stockpile; the slope angle was then calculated using the equation θ = arctan(h/r) and analysed via linear regression. The results showed that the natural angle of repose ranged from 37.80° to 40.89°, with an average of 39.29°. Linear regression indicated that pile height, particle size, and moisture content increased the angle of repose, while the base radius decreased it. Based on the stability classification, four samples were classified as less stable and two samples as unstable. This study concludes that the stability of sulphur material stockpiles is influenced by stockpile dimensions and material characteristics. The results of this study can serve as a basis for controlling the slope angle of stockpiles to minimise the risk of landslides in open storage areas.